2022
DOI: 10.1158/1078-0432.ccr-22-2661
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Associated with Altered Tumor Metabolism in Metastatic Melanoma

Abstract: Purpose: Overweight/obese (OW/OB) patients with metastatic melanoma unexpectedly have improved outcomes with immune checkpoint inhibitors (ICIs) and BRAF-targeted therapies. The mechanism(s) underlying this association remain unclear, thus we assessed the integrated molecular, metabolic, and immune profile of tumors, as well as gut microbiome features, for associations with patient BMI. Experimental Design: Associations between BMI [normal (NL < 25) or OW/OB (BMI ≥ 25] and tumor or microbiome characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The mechanisms underlying this counterintuitive phenomenon have not been fully explained, but recent clinical findings indicate that differences in tumor mutational burden (TMB) play a role 43 . Seemingly conflicting data from another study suggested that human melanoma TMB is similar between lean and obese patients 44 . However, that analysis combined over-weight and obese cohorts (BMI > 25), hindering the ability to assess how TMB is influenced specifically in patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying this counterintuitive phenomenon have not been fully explained, but recent clinical findings indicate that differences in tumor mutational burden (TMB) play a role 43 . Seemingly conflicting data from another study suggested that human melanoma TMB is similar between lean and obese patients 44 . However, that analysis combined over-weight and obese cohorts (BMI > 25), hindering the ability to assess how TMB is influenced specifically in patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have revealed that systemic metabolism significantly influences cancer cell metabolism [ 13 , 54 ]. As for primary tumors, the tumor metabolic microenvironment is determined by the cellular metabolism of tumor cells and other TME components, metabolic interactions between tumor and non-tumor cells, and their communication with the systemic metabolism of the whole body [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that excessive obesity can increase the risk of colon cancer and breast cancer, and obesity can promote tumorigenesis by stimulating inflammatory responses in the body [ 103 ]. Dark tea has been reported to lower lipids, which provides another perspective for the prevention and treatment of cancer [ 104 , 105 ].…”
Section: The Possible Anti-cancer Mechanisms Of Dark Teamentioning
confidence: 99%